THE HIMYARITE KINGDOM ON THE EVE OF AND AFTER THE ETHIOPIAN DOMINANCE IN THE SIXTH CENTURY A.D. IN THE MARTYRDOM OF ST. ARETHAS AND HIS COMPANIONS AND IN THE ACTS OF ST. GREGENTIUS - Christides, V (Journal for Semitics, 2017)
Based on two important hagiographical works written in Greek, the Martyrdom of St. Arethas and his companions and the Acts of St. Gregentius, the aim of this paper is to continue my preliminary study of the countries around the Red Sea in pre-Islamic times, especially in the sixth century A.D. The most valuable information in the Martyrdom concerns the hazardous voyage of the Ethiopian army from the main port of Adulis across the Red Sea to South Arabia (ca 525 A.D.). This work illuminates aspects of that expedition which do not appear in such detail in any other source. In addition, it describes the ports of the Red Sea in the sixth century, i.e., Klysma, Bereniki, Adulis, etc., corroborating the finds of archaeology and epigraphy. Concerning the controversial Acts of St. Gregentius, the present author has tried to discuss only some vital information reflecting the social structure of South Arabia during its Ethiopian occupation until the Persian conquest of it (ca 525 A.D. – ca 570 A.D.), and attempted to trace the origin of just one law (the treatment of animals) among those supposedly imposed on the Himyarites by the so-called archbishop Gregentius.